Data supporting: 'Thermally Dynamic Examination of Local Order in Nanocrystalline Hydroxyapatite' - Arnold, Emily (Cranfield University, 2022)
"Thermally Dynamic Examination of Local Order in Nanocrystalline Hydroxyapatite" Supporting Data Authors: Emily L Arnold*, Sarah Gosling, Samantha K Davies, Hannah L Cross, Dean S Keeble, Paul Evans, Charlene Greenwood, Keith D Rogers * email: E.L.Arnold@cranfield.ac.uk Created: 2022-05-19 ; Last revision: 2022-05-26 Underlying data is given within this dataset. A readMe is provided explaining all files given within this dataset.
Keywords: 'XRD characterization'; 'Pair Distribution Function analyses'; 'hydroxyapatite'; 'bone mineral'